Mechanistic study of nucleophilic fluorination promoted by tri-tert-butanolamine - Lee, Sung-Sik; Jung, Hyun-Kyung; Shinde, Sandip S.; Lee, Sungyul (Journal of Fluorine Chemistry, 2017)
Quantum chemical study is carried out to elucidate the mechanism of S(N)2 fluorination using. CsF promoted by tri-tert-butanolamines. Focus is on the role of the hydroxyl (OH) and the amine functional groups for accelerating the reaction. Our systematic analysis indicates that the OH groups form strong interactions with the nucleophile F-. Thus, it seems that hydrogen bonding with the nucleophile may accelerate the S(N)2 processes rather than retard them, as conventional wisdom suggests. The origin of the experimentally observed improvement of the promotor efficiency in t-butanol solvent over that in CH3CN is examined. We show that the coordination of the solvent t-butanol molecule as Lewis base on the counter-cation Cs+ lowers the Gibbs free energy of activation. (C) 2017 Elsevier B.V. All rights reserved.